Emerging Role of Exosomes in Liquid Biopsy for Monitoring Prostate Cancer Invasion and Metastasis - Gao, Zhengfan; Pang, Bairen; Li, Jing; Gao, Na; Fan, Tianli; Li, Yong (Frontiers in Cell and Developmental Biology, 2021)
Prostate cancer (PCa) is the most common solid tumor in men. While patients with local PCa have better prognostic survival, patients with metastatic PCa have relatively high mortality rates. Existing diagnostic methods for PCa rely on tissue biopsy and blood prostate-specific antigen (PSA) detection; however, the PSA test does not detect aggressive PCa. Liquid biopsy is a promising technique to overcome tumor heterogeneity in diagnosis, provide more comprehensive information, and track tumor progression over time, allowing for the development of treatment options at all stages of PCa. Exosomes containing proteins and nucleic acids are potential sources of tumor biomarkers. Accumulating evidence indicates that exosomes play important roles in cell communication and tumor progression and are suitable for monitoring PCa progression and metastasis. In this review, we summarize recent advances in the use of exosomal proteins and miRNAs as biomarkers for monitoring PCa invasion and metastasis and discuss their feasibility in clinical diagnosis.